Philanthropic Motives of China’s Celebrities in Media Representation: From an Impression Management Perspective - Gao, Jinghua; Zhang, Pengfei (Frontiers in Psychology, 2021)
Background: In China, celebrities, represented by entertainment and sports personalities, are often involved in charitable activities to assist the party-state in solving social problems. Although previous research has addressed the manifestation of prosocial behavior by Chinese celebrities, altruistic engagements have rarely been theorized from the perspective of impression management. Methods: Based on the perspective of impression management, we use the discourse analysis approach to analyze the interview manuscripts of Chinese celebrities in media reports and then summarize the charitable motives and impression management strategies adopted by Chinese celebrities in their self-presentation. Results: Chinese celebrities' self-presentation of philanthropic motives in the media can be roughly divided into five categories: motivation for empathy-altruism, motivation for social responsibility, motivation to gain prestige and pursue fame, motivation to reduce negative emotions, and motivation to achieve fulfillment and satisfaction. The philanthropic motives presented in media reports include the impression management processes of celebrities. They adopt a variety of image management strategies to self-present their philanthropic motives, and sometimes several strategies coexist. Conclusions: Our paper helps to expand the existing understanding of the relationship between impression management and philanthropy. The presentation of Chinese celebrities' philanthropic motivations in the media reflects the uniqueness of China's political, institutional, and social environment in influencing celebrity philanthropy. As a philanthropic phenomenon with Chinese characteristics, this study could provide some insights into the understanding of celebrities and philanthropy in other cultural contexts.